On the design of an optimum active mass-spring-inverted pendulum dynamic vibration absorber for the inverted pendulum type structure - Sang, Nguyen Chi; Thang, Nguyen Cao (Vietnam Journal of Mechanics, 2008)
A Dynamic Vibration Absorber (DVA) is appropriate equipment for vibration control in many kinds of engineering. In general, there are two main types of DVAs: the passive DVAs and the active DVAs. The paper presents a design of an active mass-spring-inverted pendulum DVA for the inverted pendulum type structure in case the external force is white noise process. The design is based on the optimum passive DVA as carried out in [4] and apply the optimum control force by minimizing the performance index. Numerical simulation which is done for an inverted pendulum structure in the ocean in three cases without DVA, with passive DVA, with active DVA shows that the active DVA is better than the passive one.